Step
*
1
of Lemma
formal-sum-mul-1
1. S : Type
2. K : Rng
3. x : bag(|K| × S)
⊢ bag-map(λp.let k',s = p in <1 * k', s>x) = x ∈ bag(|K| × S)
BY
{ (Assert bag-map(λp.let k',s = p in <1 * k', s>x) = bag-map(λp.p;x) ∈ bag(|K| × S) BY
         (EqCDA THEN FunExt THEN Auto THEN D -1 THEN Reduce 0 THEN Auto)) }
1
1. S : Type
2. K : Rng
3. x : bag(|K| × S)
4. x2 : |K|
5. x3 : S
⊢ <1 * x2, x3> = <x2, x3> ∈ (|K| × S)
2
1. S : Type
2. K : Rng
3. x : bag(|K| × S)
4. bag-map(λp.let k',s = p in <1 * k', s>x) = bag-map(λp.p;x) ∈ bag(|K| × S)
⊢ bag-map(λp.let k',s = p in <1 * k', s>x) = x ∈ bag(|K| × S)
Latex:
Latex:
1.  S  :  Type
2.  K  :  Rng
3.  x  :  bag(|K|  \mtimes{}  S)
\mvdash{}  bag-map(\mlambda{}p.let  k',s  =  p  in  ə  *  k',  s>x)  =  x
By
Latex:
(Assert  bag-map(\mlambda{}p.let  k',s  =  p  in  ə  *  k',  s>x)  =  bag-map(\mlambda{}p.p;x)  BY
              (EqCDA  THEN  FunExt  THEN  Auto  THEN  D  -1  THEN  Reduce  0  THEN  Auto))
Home
Index